Long Non-Coding RNAs, Novel Offenders or Guardians in Multiple Sclerosis: A Scoping Review - Jalaiei, Abbas; Asadi, Mohammad Reza; Sabaie, Hani; Dehghani, Hossein; Gharesouran, Jalal; Hussen, Bashdar Mahmud; Taheri, Mohammad; Ghafouri-Fard, Soudeh; Rezazadeh, Maryam (Frontiers in Immunology, 2021)
Multiple sclerosis (MS), a chronic inflammatory demyelinating disease of the central nervous system is one of the most common neurodegenerative diseases worldwide. MS results in serious neurological dysfunctions and disability. Disturbances in coding and non-coding genes are key components leading to neurodegeneration along with environmental factors. Long non-coding RNAs (lncRNAs) are long molecules in cells that take part in the regulation of gene expression. Several studies have confirmed the role of lncRNAs in neurodegenerative diseases such as MS. In the current study, we performed a systematic analysis of the role of lncRNAs in this disorder. In total, 53 studies were recognized as eligible for this systematic review. Of the listed lncRNAs, 52 lncRNAs were up-regulated, 37 lncRNAs were down-regulated, and 11 lncRNAs had no significant expression difference in MS patients compared to controls. We also summarized some of the mechanisms of lncRNAs functions in MS. The emerging role of lncRNAs in the neurodegenerative diseases suggests that their dysregulation could trigger neuronal death via still unexplored RNA-based regulatory mechanisms. Evaluation of their diagnostic significance and therapeutic potential could help in design of novel treatments for MS.